2016
DOI: 10.1080/09515089.2016.1174843
|View full text |Cite
|
Sign up to set email alerts
|

Moral objectivism across the lifespan

Abstract: We report the results of a cross-sectional study that examined folk metaethical judgments in participants between the ages of 12 and 88. We found that participants in their late teens and early twenties attributed less objectivity to ethical statements than participants in older or younger age groups. We also critically examine other recent investigations of folk metaethical intuitions and compare our results to certain well-known findings in the moral development literature.keywords: moral psychology, metaeth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…A number of existing studies have explored people's intuitions about the conditions under which moral claims have exclusionary content (Beebe & Sackris , Fisher et al . forthcoming, Goodwin & Darley , , Nichols , Sarkissian et al .…”
Section: Disagreement Without Exclusionmentioning
confidence: 99%
“…A number of existing studies have explored people's intuitions about the conditions under which moral claims have exclusionary content (Beebe & Sackris , Fisher et al . forthcoming, Goodwin & Darley , , Nichols , Sarkissian et al .…”
Section: Disagreement Without Exclusionmentioning
confidence: 99%
“…Further research is required to determine whether it is concreteness or other social factors that push individuals in the direction of greater objectivism. The studies reported above show that not only are there differences in folk metaethical judgments that track the content of ethical claims (Goodwin & Darley, 2008;Beebe & Sackris, under review; Study 1), how contested they are (Goodwin & Darley, 2012;Study 2), and the cultural distance between disagreeing parties (Sarkissian et al, 2011); there are also differences that track the goodness or badness of disagreeing parties (Study 5) and possibly their concreteness as well (Studies 3 and 4). It is hoped that the present research sheds useful light on the multi-dimensional variation that characterizes the folk metaethical landscape.…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, responses are deemed “objectivist” when participants judge that, in cases of disagreement, at least one party to the disagreement must be wrong; conflicting claims cannot both be correct. These studies consistently show that very few people give objectivist responses on aesthetic matters, and people are much more likely to be objectivist about putatively moral issues (Beebe & Sackris 2016; Goodwin & Darley 2008; 2012; Wright et al 2013). (Unfortunately, none of these studies has examined objectivism for epistemic matters.)…”
mentioning
confidence: 87%